An Evaluation of Students’ Readiness to Use E-learning Media in the MBKM Program - Humairah Humairah; Uswatun Chasanah; Eko Handoyo (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to prepare the readiness of students to use E-learning media in the MBKM (Freedom to Learn – Independent Campus) program at the Faculty of Science, Technology and Education. This was an evaluation research with a quantitative research approach and descriptive method. The data collection technique used lecturer and student questionnaires based on the CIPP evaluation model (context, input, process, product). The samples were 98 students. The results indicated that in terms of readiness and understanding of E-learning-based learning management, the lecturers were included in the high category with a percentage of 87.78%. The score obtained by students based on the understanding of E-learning-based learning was included in the high category with a percentage of 82.16%. The results of the questionnaire showed that the E-learning-based learning activities were carried out well (structured, according to schedule and coordinated).